PENGATUR KECEPATAN MOTOR DC DENGAN SENSOR SUHU BERBASIS MIKROKONTROLER ATMEGA16 - Prawiroredjo, Kiki; Rahardjo TS, Kuat; Stevanus, Stevanus (Jurnal Teknik Elektro, 2009)
A telecommunication cabinet usually uses a Direct Current fan with a Direct Current motor (DC motor) to make the cabinet temperature does not exceed the temperature that is allowed. Using a DC motor has weaknesses because it always rotates in full speed although the temperature in the cabinet gets down already. It causes inefficiency of the power consumption and the DC motorâs lifetime is not long enough.The prototype of DC motor speed controller controls the speed of a DC motor with the temperature environment as its reference. This circuit is built by a temperature sensor LM35, a microcontroller ATmega16 as the processor that analizes the input from the temperature sensor and relays. This prototype is equipped with a Liquid Crystal Display (LCD) to display the temperature of the cabinet and the DC motor speed. After the prototype is assembled and tested, it is known that the circuit controls a DC motor speed according to the changes of the temperature that has been determined by the software program. The DC motor stops rotating if the temperature sensor senses the temperature below the minimum temperature level.Keywords: DC motor, temperature sensor, LCD, microcontroller